Evaluating The Accuracy Of Digital Terrain Model In Palestine (West Bank) - Qurneh, Mahmoud; Fataftah, Mohammad (جامعة بوليتكنك فلسطين - كلية الهندسة - مساحة, 2015)
نموذج االرتفاعات الرقمي )Digital Elevation Modle( ، هو عبارة عن نموذج رقمي يمثل االرتفاعات المختلفة فوق سطح االرض ، أما اذا كان هذا النموذج يمثل تضاريس فقط يدعى بنموذج التضاريس الرقمي ) Digital Terrain Model( ، وعادة ما يتم انشاء هذه النماذج الرقمية المحليه من خالل المساحة االرضية او من خالل التصوير الجوي ، أما النماذج العالمية فيتم انشاؤها من خالل صور وبيانات مأخوذة من االقمار الصناعية ،وهذه النماذج يتم أستخدمها كمراجع من قبل المهندسين او الطلبة . من النادر مناقشة دقة هذه النماذج ،لذلك فان مشروعنا يهدف الى فحص دقة هذه النماذج الرقمية لالرتفاعات المستخدمة في فلسطين ،سواء العالمية او المحلية ، وتم تحقيق ذلك من خالل قياس ارتفاعات لعدد من النقاط المرجعيه في فلسطين ومقارنتها مع تلك التى يتم الحصول عليها من خالل النماذج الرقمية الرتفاعات التضاريس )DTM(. Digital elevation model (DEM) is a 3D digital representation for heights above the earth surface. If the surface is representing the terrain, then it called digital terrain model (DTM). Local DTM are often created by surveying or photogrammetry methods. While global DTM are mostly created by means of satellite images, Altimetry or LidAR. These models are commonly used by people, engineers and students. The accuracy of these DTM models are rarely discussed. Different models have different spatial resolution or contour intervals. But their accuracy are not truly introduced. Our objective in this project is to evaluate the existing accuracy of the global or photogrammetric DTMs that are being commonly used in Palestine. This can be achieved by measuring the heights of a group of reference points all over Palestine (West Bank) and comparing their measured heights with the heights obtained from the DTM.
no of pages 103 ,28831, مساحة 1/2015 , in the store
Keywords: Digital Terrain Model